Effect of axial loading on cold-formed steel wall panels with fibre-cement and calcium silicate boards sheathing: Experimental and analytical studies. (December 2021) - Sonkar, Chanchal; Kumar Bhattacharyya, Sriman; Kumar Mittal, Achal
Abstract: Sheathed Cold-formed Steel (CFS) wall framed buildings provide various advantages such as speed of construction, environmentally green, high strength-to-weight ratio etc. over construction with conventional materials. In this type of construction, walls are the main load-bearing elements. It has been observed in literature that sheathing significantly influences the load-carrying capacity of CFS wall frame. However, limited studies are available on axial behaviour of calcium silicate board (CSB) sheathed CFS wall panels. Fibre cement board (FCB) sheathed wall panels are proposed in the present study and the same are investigated for their performance under axial loading. A detailed series of experiments on full-scale sheathed perforated CFS single-studed wall panels are carried out and load factors which may be adopted by designers or researchers for evaluating axial strength of sheathed CFS panels, are proposed. Sheathings using FCB and CSB boards are applied on the specimens. Effect of variation of parameters such as type of sheathing, sheathing thickness, layer configuration of sheathing (number of layer on either side) on the load factors are also investigated in the present study. 'Differential equation of equilibrium' based analytical method is validated with the experimental results in the present study. In the adopted analytical method, the stud is assumed as channel section restrained by sheathing based springs. The value of spring stiffnesses is obtained analytically as specified in the literature, using modulus of elasticity, obtained through experiments. Suitable modification factor is recommended for panels with sheath on one side, while predicting axial strength of CFS panels with sheath, analytically. The proposed factor may be used with confidence as the experimental results agree well with the analytical results.